SLC39A1 contributes to gemcitabine resistance of pancreatic ductal adenocarcinoma by activating AMPK signaling (Bangladesh Journal of Pharmacology, 2024)
Gemcitabine is a common first-line chemotherapy agent, but gemcitabine resistance is a clinical challenge for pancreatic ductal adenocarcinoma patients. Solute carrier 39A1 (SLCA39A1) as a zinc regulator presents a crucial function in the modulation of malignancy progression. Here, the impact of SLC39A1 on the gemcitabine resistance of pancreatic ductal adenocarcinoma was investigated. Immunohistochemistry demonstrated that the SLC39A1 expression was significantly up-regulated in gemcitabine-resistant pancreatic ductal adenocarcinoma samples compared with gemcitabine-sensitive ones. Gemcitabine dose-dependently inhibited the viability of the cancer cells, and SLC39A1 knockdown aggravated this effect. Both mRNA and protein expression of SLC39A1 were elevated in the gemcitabine-resistant cancer cells. SLC39A1 knockdown also reversed AMP-activated protein kinase (AMPK) phosphorylation and S6K expression of cancer cells regulated by the gemcitabine resistance. SLC39A1 promotes gemcitabine resistance of pancreatic ductal adenocarcinoma by activating AMPK signaling, revealing SLC39A1 may be a potential target in patients with gemcitabine resistance.